2016
DOI: 10.1515/cclm-2015-0431
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of serum free light chain levels in healthy adults immediately after marathon running

Abstract: Background: Immunoglobulin κ and λ free light chains (FLC) are important serum biomarkers for diagnosing and monitoring plasma cell dyscrasias (via the κ:λ FLC ratio), and assessing immune competence and activation status (via ∑FLC). FLCs are produced, in excess of heavy chains, from healthy plasma cells during immunoglobulin production, but unlike intact immunoglobulins that are cleared by cellular catabolism over a number of weeks, FLC are rapidly cleared from the bloodstream by the renal glomerulus with a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
(32 reference statements)
1
4
0
Order By: Relevance
“…This might be due to the alteration of FLC λ is not consistent with FLC κ. Similar phenomenon was observed in healthy adults completed marathon running ( 46 ), which may induce acute and transient renal impairment ( 47 ). Further study is needed to explore why and how gut microbiome stimulate FLC λ.…”
Section: Discussionsupporting
confidence: 69%
“…This might be due to the alteration of FLC λ is not consistent with FLC κ. Similar phenomenon was observed in healthy adults completed marathon running ( 46 ), which may induce acute and transient renal impairment ( 47 ). Further study is needed to explore why and how gut microbiome stimulate FLC λ.…”
Section: Discussionsupporting
confidence: 69%
“…This study observed that daily life activities had an impact on increasing levels of immunoglobulins such as IgM. Studies have shown that exercise increases immunoglobulin, which may be due to exercise-induced immune activation or immunoglobulin redistribution ( Campbell et al, 2016 ). Similarly, this study shows that daily activities can induce immune activation by increasing IgM levels.…”
Section: Discussionmentioning
confidence: 84%
“…Although these high levels may be the result of the presence of another, non‐atopic disease, these subjects were apparently healthy and reported no medical conditions. Elevated serum Ig‐FLC levels have been shown in multiple myeloma [15 ], systemic lupus erythematosus [16 ], and rheumatoid arthritis patients [17 ], and were also reported shortly after marathon running [18 ].…”
Section: Discussionmentioning
confidence: 99%